Identifikasi dan Kelimpahan Populasi Lalat Pengorok Daun(Liriomyza spp.) (Diptera: Agromizydae) pada Tanaman Bawang Merah (Alium ascalonicum L.) dan Bawang Daun (Allium fistolosum L.) - MAHARDIKA, ANAK AGUNG NGURAH; SUPARTHA, I WAYAN; DARMIATI, NI NENGAH (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology); Vol.8, No.4, Oktober 2019, 2019)
Identification and Population Abundance of Leaf Miner (Liriomyza spp.) (Diptera: Agromyzidae) on Onion Plant (Alium ascalonicum L.) and Welsh Onion (Allium fistolosum L.) This research was conducted in order to determine the species and abundance population of leaf miner which attacked the onion plant (Alium ascalonicum L.) and welsh onion (Allium fistolosum L.). The sample in this research was taken by purposive method by taking 100 leaves per species of onion in Bangli and Tabanan Regencies. The leaf sample was reared in a bottle container and the emerged adult insects of the leaf miner were identified morphologically. The results showed the leaf miner species that attacked onions plant and welsh onion were Liriomyza chinensis and Liriomyza huidobrensis. The leaf miner species found on onion plant in Songan Village, Bangli Regency was L. chinensis with an abundance of 100% (324 adult insects). Meanwhile, in Batusesa Village, Tabanan Regency, which is the center of welsh onion production, two species of leaf miner were found, namely L. chinensis and L. huidobrensis with an abundance of L. chinensis 97.0% (258 adult insects) and L. huidobrensis 3.0% (8 adult insects). In generally, L. chinensis is a species of leaf miner which dominate the onion plantations.